PENGARUH MODEL EXPERIENTIAL LEARNING BERBANTUAN APLIKASI TIKTOK TERHADAP KEMAMPUAN SISWA MENULIS TEKS ANEKDOT KELAS X DI SMK SANTO PAULUS MEDAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effect of the Experiential Learning model assisted by the TikTok application on the ability to write anecdote texts among Grade X students at SMK Santo Paulus Medan. The methodology used in this study is a quantitative research approach. The study population consisted of all Grade X students at SMK Santo Paulus Medan, totaling 31 students. The sampling technique used was purposive sampling, in which Class X TKJ with 31 students was selected as the research sample. The instrument used was a subjective test in the form of an essay. After the treatment was administered, the mean pretest score was 64.84 with a standard deviation of 9.36, and the mean posttest score was 77.4 with a standard deviation of 8.21. The prerequisite tests indicated that the sample was normally distributed and homogeneous. A paired sample t-test was then conducted at a significance level of (α = 0.05). The results yielded a t-count of 5.66 and a t-table value of 2.000 (df = 60). Since t-count (5.66) > t-table (2.000), it can be concluded that there is a significant effect of the Experiential Learning model assisted by the TikTok application on the ability to write anecdote texts among Grade X students at SMK Santo Paulus Medan. The final scores obtained fall under the good assessment category. Keywords: Experiential Learning Model, TikTok Application, writing ability, anecdote text.